Stabilization of flaxseed oil nanoemulsions based on flaxseed gum: Effects of temperature, pH and NaCl on stability. (15th February 2023) - Sun, Hongtao; Ma, Yan; Huang, Xianqing; Song, Lianjun; Guo, Hongtao; Sun, Xiaodong; Li, Ning; Qiao, Mingwu
Abstract: In this study, flaxseed oil was used as embedding material and flaxseed gum as sole emulsifier to prepare flaxseed oil nanoemulsions. The storage temperature (4–37 °C, pH 5.8, 0 mmol/L), pH (3–11, 4 °C, 0 mmol/L), NaCl (100–500 mmol/L, pH 5.8, 4 °C) on the stability of flaxseed oil nanoemulsions were investigated in terms of particle size, ζ -potential, creaming index, microscopy, rheological characteristics, surface tension, and nanoemulsion color as characterization. The results showed that temperature significantly affected the stability of flaxseed oil nanoemulsions, and the stability decreased with increasing temperature. The characteristics of flaxseed oil nanoemulsion were relatively stable at pH 5 and pH 7, while the stability was poor under pH 3 and alkaline conditions. As the strength of the ionic increased, unstable aggregation occurred (NaCl >200 mmol/L). In conclusion, the stability of flaxseed oil nanoemulsion was better at 4 °C, pH 5–7, and NaCl <200 mmol/L. These results provide useful information to facilitate the design and preparation of stable package delivery systems for flaxseed oil in food and other industries. Graphical abstract: Image 1 Highlights: Flaxseed oil nanoemulsions (FON) were prepared based on homologous flaxseed gum. Multi-indicator evaluation of the impact of environmental changes on FON stability. Temperature significantly affected characterizations and stability of FON. FON droplets were more aggregated at high NaCl concentrations and alkaline pH.